Loss of succinyl-CoA synthase ADP-forming β subunit disrupts mtDNA stability and mitochondrial dynamics in neurons - Yujun Zhao (Nature Portfolio, 2017)
Abstract Succinyl Coenzyme A synthetase (SCS) is a key mitochondrial enzyme. Defected SCS ADP-forming β subunit (SCS A-β) is linked to lethal infantile Leigh or leigh-like syndrome. However, the impacts of SCS A-β deficiency on mitochondria specifically in neurons have not yet been comprehensively investigated. Here, by down-regulating the expression levels of SCS A-β in cultured mouse neurons, we have found that SCS A-β deficiency induces severe mitochondrial dysfunction including lowered oxidative phosphorylation (OXPHOS) efficiency, increased mitochondrial superoxide production, and mtDNA depletion as well as aberrations of mitochondrial fusion and fission proteins, which eventually leads to neuronal stress. Our data also suggest that the deregulation of mitochondrial nucleoside diphosphate kinase (NDPK) together with defects in mitochondrial transcription factors including mitochondrial DNA pol γ and Twinkle contribute to SCS A-β deficiency-mediated mtDNA instability. Furthermore, we have found that SCS A-β deficiency has detrimental influence on neuronal mitochondrial dynamics. Put together, the results have furnished our knowledge on the pathogenesis of SCS A-β deficiency-related mitochondrial diseases and revealed the vital role of SCS A-β in maintaining neuronal mitochondrial quality control and neuronal physiology.